Study of Streptomyces spp. to control purple blotch disease caused by Alternaria porri in shallot plant - Risdiyanti, Rateh Lailatul; Rahmadhini, Noni; Suryaminarsih, Penta; Mujoko, Tri (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2023)
Alternaria porri is a fungal pathogen that causes purple blotch on shallots, this fungus can cause crop yield loss of 3 – 57%. A. porri was obtained from the Sumber Brantas onion farm and then isolated by planting infected tissue. Streptomyces spp. is a filamentous bacterium that is abundant in the soil and can be used as a biological agent, decomposer and plant growth promote. Streptomyces spp. was obtained one isolate from shallot land location in Pare, Kediri, East Java (BMP: Bawang Merah Pare) and three isolates from Sidera, Palu, Central Sulawesi (BMS: Bawang Merah Sidera) (BMS1, BMS2, BMS3). The purpose of this study was to determine the efficacy of Streptomyces spp. to control A porri consist of in vitro and In vivo antagonist test. Antagonist test was carried out by dual culture method and the Streptomyces spp. which can inhibit the development of A porri would be used antagonist test in vivo. The study was designed using a Factorial Complete Randomized Design with two factors, candidate isolates of biological control agents and concentrations of Streptomyces spp. be diluted into 5%, 10%, and 15%, it will applied on shallot plant Bauji variety. The results of the In vitro test shown the highest inhibition zone from BMP 17.75% while BMS1 13.75%, BMS2 8,75%, and 8.50%. in vivo test shown lowest disease severity value in BMP 15% concentration was 1.13% while diseases severity of BMS1 was 1.27%, and BMS2 was 1.80%. Therefore, Streptomyces spp. has potency as an alternative pesticide for sustainable agriculture.